Hydroxychloroquine inhibits proinflammatory signalling pathways by targeting endosomal NADPH oxidase. Issue 5 (30th November 2016) - Müller-Calleja, Nadine; Manukyan, Davit; Canisius, Antje; Strand, Dennis; Lackner, Karl J
Abstract : Objectives: Hydroxychloroquine (HCQ) has been used for decades to treat patients with rheumatic diseases, for example, systemic lupus erythematosus (SLE), rheumatoid arthritis or the antiphospholipid syndrome (APS). We hypothesise that HCQ might target endosomal NADPH oxidase (NOX), which is involved in the signal transduction of cytokines as well as antiphospholipid antibodies (aPL). Methods: For in vitro experiments, monocytic cells were stimulated with tumour necrosis factor α (TNFα), interleukin-1β (IL-1β) or a human monoclonal aPL and the activity of NOX was determined by flow cytometry. The expression of genes known to be induced by these stimuli was quantified by quantitative reverse transcription PCR. Live cell imaging was performed by confocal laser scanning microscopy. Finally, the effects of HCQ on NOX-induced signal transduction were analysed in an in vivo model of venous thrombosis. Results: HCQ strongly reduces or completely prevents the induction of endosomal NOX by TNFα, IL-1β and aPL in human monocytes and MonoMac1 cells. As a consequence, induction of downstream genes by these stimuli is reduced or abrogated. This effect of HCQ is not mediated by direct interference with the agonists but by inhibiting the translocation of the catalytic subunit of NOX2 (gp91phox) into the endosome. In vivo, HCQ protects mice from aPL-induced and NOX2-mediated thrombus formation. Conclusions: We describe here a novel mechanism of action of HCQ, that is, interference with the assembly of endosomal NOX2. Since endosomal NOX2 is involved in many inflammatory and prothrombotic signalling pathways, this activity of HCQ might explain many of its beneficial effects in rheumatic diseases including the APS.